When suppliers shift my boundaries: Supplier employee mobility and its impact on buyer firms' sourcing strategy - Chondrakis, G; Sako, M (Wiley, 2020)
Research summary: Buyer firms respond to supplier employee mobility by reshuffling work among suppliers. However, the extant literature has not considered plural-sourcing firms which can bring work back in-house. In this paper, we develop a governance framework in which buyers engage in a comparative assessment of the costs associated with different sourcing modes following supplier employee mobility. Due to the imperfect transferability of social capital and associated uncertainty, buyers face increased contracting costs when supplier employees move. This prompts plural-sourcing buyers to increase their reliance on insourcing when the costs of adjusting in-house capacity are relatively low and when the costs of switching to alternative suppliers are relatively high. The analysis of data on patent prosecution activities and patent attorney mobility provides support to our theory.